2010
DOI: 10.1016/j.molcel.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear-Retained Noncoding RNA MALAT1 Regulates Alternative Splicing by Modulating SR Splicing Factor Phosphorylation

Abstract: SUMMARY Alternative splicing (AS) of pre-mRNA is utilized by higher eukaryotes to achieve increased transcriptome and proteomic complexity. The serine/arginine (SR) splicing factors regulate tissue- or cell-type-specific AS in a concentration- and phosphorylation-dependent manner. However, the mechanisms that modulate the cellular levels of active SR proteins remain to be elucidated. In the present study, we provide evidence for a role for the long nuclear-retained regulatory RNA (nrRNA), MALAT1 in AS regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
1,742
5
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,947 publications
(1,819 citation statements)
references
References 63 publications
55
1,742
5
17
Order By: Relevance
“…They contain transcription factors, 3 0 -end RNA processing factors, translation regulation factors and the large subunit of RNA polymerase II. 28,29 Jia et al have shown also that the inhibition of transcription changes the nucleoplasmic distribution of FTO, which becomes more concentrated at speckles. Of note, we observed different pattern of nucleoplasmic FTO staining in cells with different proliferation rates.…”
Section: Discussionmentioning
confidence: 99%
“…They contain transcription factors, 3 0 -end RNA processing factors, translation regulation factors and the large subunit of RNA polymerase II. 28,29 Jia et al have shown also that the inhibition of transcription changes the nucleoplasmic distribution of FTO, which becomes more concentrated at speckles. Of note, we observed different pattern of nucleoplasmic FTO staining in cells with different proliferation rates.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the abundant, nuclear-retained, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1; a.k.a. Neat2) is highly conserved in mammals and localized to nuclear speckles led the Prasanth laboratory to investigate the involvement of this non-coding (nc) RNA in pre-mRNA metabolism (54). They found that MALAT1 does not play a role in the formation and maintenance of nuclear speckles but instead, it interacts with a sub-set of SR proteins modulating their sub-nuclear distribution and even more intriguingly, influencing the cellular levels and the ratio of phosphorylated versus de-phosphorylated SR proteins.…”
Section: Post-translational Modifications Of Sr Proteins: Above and Bmentioning
confidence: 99%
“…Dual RNA FISH and immunofluorescence using probes against MALAT1, U2‐snRNA, and antibodies against SR splicing factor, SRSF1, have been used to clarify the role of MALAT1 in RNA splicing. MALAT 1 was shown to be co‐localized to nuclear speckles with SR splicing factors 48.…”
Section: Methods Used To Localize Lncrnas Inside the Cellmentioning
confidence: 99%